The The potency of mackerel scad (Decapterus macarellus) caught in WPP 716 of North Sulawesi waters by Purse Seiner landed at the coastal fishing port of Tumumpa, Manado - Gahunting, Dedy; Sitanggang, Effendi. P; Dien, Heffry. V (Jurnal Ilmiah PLATAX, 2023)
The research aims to analyze the potentiality of MSY, total allowable catch (TAC), optimum effort (EMSY), and CPUE, based on the annual official report of catch and effort during 2018 - 2022 and some biological aspects of 100 fishes taken at random as samples. The results showed, the highest catch was in 2021 of 4,776,970 tons with an effort of 22,216 trips, and the lowest in 2018 of 1.610.792 tons with an effort of 14.805 trips. The MSY was 4.374.723 tons/year with a TAC of 3.499.779 tons/year and an EMSY of 20,184 trip/year. Using α 5%, it resulted in an average length of 20,64 ± 0.40 cm, and an average weight of 146.16 ± 9.98 g, with W = 0,2388 L2,1115 (W weight, L length). categorized a negative allometric growth (b < 3), with K (condition factor) 1.01 ± 0.10, and sex ratio (male and female) was 1.38: 1. The 42 female fishes had an average length of 21.09 ± 0.50 cm, average weight 154.50 ± 12.30 g, with W = 0,0061 L3.3172, categorized an isometric growth (b = 3) with K 1.00 ± 0.01, while the 58 male fishes had an average length of 20.31 ± 0.57 cm, average weight 140.12 ± 9.99 g, with W = 0,7748 L1.7313, categorized a negative allometric growth (b < 3) with K 1.02 ± 0.05. Keywords: Decapterus macarellus, WPP 716, purse seiners, MSY, length-weight relationship, coastal fishing port, Tumumpa Manado Abstrak Penelitian ini bertujuan menganalisis potensi MSY dan jumlah tangkapan yang diperbolehkan (JTB), upaya pemanfaatan optimum, tingkat pemanfaatan MSY, serta menganalisis beberapa aspek biologis ikan layang biru hasil tangkapan pukat cincin ini, melalui pengambilan 100 ekor sampel acak. Hasil penelitian menunjukkan jumlah tangkapan tertinggi tahun 2021 yaitu 4.776.970 ton dengan upaya penangkapan 22.216 trip, dan terendah tahun 2018 dengan jumlah tangkapan 1.610.792 ton dengan upaya 14.805 trip. Potensi maksimum lestari (CMSY) ikan ini tercatat 4.374.723 ton/tahun dan JTB 3.499.779 ton/tahun dengan upaya maksimum lestari (EMSY) 20.184 trip/tahun. Menggunakan α 5%, diperoleh panjang rerata 20,64 ± 0.40 cm, berat rerata 146.16 ± 9.98 g dengan hubungan) yaitu W = 0,2388 L2,1115 (berat (W berat, L panjang cagak) yang terkategori alometrik negatif (b < 3), dengan K (faktor kondisi)) 1.01 ± 0.10 , dan nisbah kelamin antara jantan dan betina tercatat 1,38 : 1. Ikan layang betina (n = 42) memiliki panjang rerata 21.09 ± 0.50 cm, berat rerata 154.50 ± 12.30 g, dengan hubungan W = 0,0061 L3.3172 yang terkategori isometrik (b = 3) dengan K = 1.00 ± 0.01, sementara 58 ikan jantan memiliki panjang rerata 20.31 ± 0.57 cm, berat rerata 140.12 ± 9.99 g, dengan hubungannya W = 0,7748 L1.7313 terkategori alometrik negatif (b < 3) dengan K 1.02 ± 0.05. Kata kunci : Ikan layang biru (Decapterus macarellus), MSY, hubungan panjang-berat, faktor kondisi, PPP Tumumpa